Substance use, affective symptoms, and suicidal ideation among Russian, Somali, and Kurdish migrants in Finland - Salama Essi; Castaneda Anu E; Suvisaari Jaana; Rask Shadia; Laatikainen Tiina; Niemelä Solja (SAGE PUBLICATIONS LTD, 2022)
Comorbidity of substance use with affective symptoms and suicidality has been well documented in the general population. However, population-based migrant studies about this association are scarce. We examined the association of affective symptoms and suicidal ideation with binge drinking, daily smoking, and lifetime cannabis use among Russian, Somali, and Kurdish migrants in comparison with the Finnish general population. Cross-sectional data from the Finnish Migrant Health and Wellbeing Study (Maamu, n = 1307) and comparison group data of the general Finnish population (n = 860) from the Health 2011 Survey were used. Substance use included self-reported current binge drinking, daily smoking, and lifetime cannabis use. Affective symptoms and suicidal ideation were measured using the Hopkins Symptom Checklist-25 (HSCL-25). We performed multivariate logistic regression analyses, including age, gender, and additional socio-demographic and migration-related factors. Suicidal ideation (OR 2.4 95% CI 1.3-4.3) was associated with binge drinking among Kurds and lifetime cannabis use among Russians (OR 5.6, 95% CI 1.9-17.0) and Kurds (OR 5.5, 95% CI 1.9-15.6). Affective symptoms were associated with daily smoking (OR 1.6, 95% CI 1.02-2.6) and lifetime cannabis use (OR 6.1, 95% CI 2.6-14.5) among Kurdish migrants. Our results draw attention to the co-occurrence of suicidal ideation, affective symptoms, and substance use, especially among Kurdish migrants. These results highlight the variation of comorbidity of substance use and affective symptoms between the different populations. This implies that screening for substance use in mental healthcare cannot be neglected based on presumed habits of substance use.